THE WIZARDS PROGRAM AT MERCY COLLEGE - Sax, Boria (Online Learning, 2003)
Mercy College has encouraged students to take a more active role in their education through the use of online teaching assistants or “course wizards.” The duties of wizards include tutoring students, facilitating discussion, and locating resources, but their most essential function is to model the role of a successful student. Having successfully confronted the challenges of a college environment, they provide peers with the benefits of their experience. The program takes advantage of the special intimacy that students share with their classmates. This article gives an outline of the wizards program, and examines it with respect to several criteria including student satisfaction, learning effectiveness, faculty satisfaction, and the satisfaction of the wizards themselves.